Multifunctional lubricating oil additive as well as preparation method and application thereof

By forming a covalent organic frame on the surface of Ti3C2, the dispersion stability problem in the base oil is solved, the friction coefficient and wear rate are reduced, the lubricating performance is improved, and high-quality lubricating oil additives are achieved.

CN119285976APending Publication Date: 2025-01-10QUFU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458934.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Ti3C2 is a lubricating oil additive in the base oil with poor dispersion stability, resulting in high friction coefficient and wear rate.

Method used

By placing Ti3C2 with tris(4-aminophenyl)amine and 3,6-bis(5-aldehydethiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4- c]Pyrrole-1,4(2H,5H)-dione mixes to form a covalent organic frame, increase the layer spacing of Ti3C2 and form a barrier on its surface, improving its dispersion stability and lubricating properties.

Benefits of technology

It significantly reduces the friction coefficient and wear rate, improves the dispersion stability and friction-reduction and anti-wear properties of lubricating oil, and is simple and economical in the preparation method, and meets the requirements of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285976A_ABST
    Figure CN119285976A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a multifunctional lubricating oil additive and a preparation method and application thereof, and the preparation method comprises the following steps: mixing Ti3C2 with tris (4-aminophenyl) amine and a solvent A to obtain a mixed solution B; the mixed solution B is mixed with 3, 6-bis (5-formylthiophene-2-yl)-2, 5-bis (2-ethylhexyl) pyrrolo [3, 4-c] pyrrole-1, 4 (2H, 5H)-diketone and a solvent B to be subjected to a covalent organic framework synthesis reaction, and the lubricating oil additive is obtained.The lubricating oil additive obtained through the preparation method can increase the interlamellar spacing of Ti3C2, a barrier is formed on the Ti3C2, and therefore the lubricating oil additive has the advantages that the lubricating oil additive has a good lubricating effect on the Ti3C2, the service life of the lubricating oil additive is prolonged, the service life of the lubricating oil additive is prolonged, the service life of the lubricating oil additive is prolonged, and the service life of the lubricating oil additive is prolonged. The problem that the dispersion stability of Ti3C2 serving as a lubricating oil additive in base oil is poor can be solved, and the friction coefficient and the wear rate can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nano-functional materials and mechanical lubrication technology, and more specifically, to a multifunctional lubricating oil additive and a preparation method and application thereof. Background Art

[0002] When two mechanical parts come into contact, friction occurs, consuming energy and increasing the wear of the equipment. Lubrication plays a vital role in the field of mechanical engineering. It involves reducing friction and wear between mechanical parts, thereby improving the operating efficiency of the equipment, extending its service life, and reducing maintenance costs. In order to achieve these goals, researchers have developed various types of lubricating materials, among which two-dimensional (2D) materials have been widely used as lubricant additives, such as graphene and its derivatives, molybdenum disulfide and other materials. These two-dimensional layered materials have high intralayer strength and weak interlayer shear force. Thanks to the high specific surface area, it is easy to achieve interlayer slip during friction, and have a strong load-bearing capacity, and form a stable lubricating protective film between the friction pairs to reduce friction and wear.

[0003] Ti3C2 has attracted extensive attention as a nano-lubricant additive and solid lubricant coating. Although it has great potential in tribology, its dispersion stability in base oil as a lubricant additive is poor due to the large number of hydrophilic groups on its surface. Summary of the invention

[0004] The present application is provided to solve the above-mentioned defects existing in the prior art. A multifunctional lubricant additive and its preparation method and application are needed to increase the interlayer spacing of Ti3C2 and form a barrier on Ti3C2 to avoid its own accumulation, which can solve the problem of poor dispersion stability of Ti3C2 in base oil as a lubricant additive and reduce the friction coefficient and wear rate.

[0005] In a first aspect of the present application, a method for preparing a multifunctional lubricating oil additive is provided, the preparation method comprising: mixing Ti3C2 with tri(4-aminophenyl)amine and solvent A to obtain a mixed solution B; mixing the mixed solution B with 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione and solvent B to carry out a covalent organic framework synthesis reaction to obtain a lubricating oil additive.

[0006] In a second aspect of the present application, a lubricating oil additive prepared by the preparation method described in any embodiment of the present application is provided.

[0007] The third aspect of the present application provides a use of the lubricating oil additive described in any embodiment of the present application in lubricating oil.

[0008] The multifunctional lubricating oil additive and preparation method provided in each embodiment of the present application are as follows: Ti3C2 is first mixed with tri(4-aminophenyl)amine to allow tri(4-aminophenyl)amine to be adsorbed onto the Ti3C2 nanosheets, and then mixed with 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione to perform in situ synthesis of a covalent organic framework on the Ti3C2 nanosheets, thereby increasing the interlayer spacing of the Ti3C2 nanosheets without changing the layered structure of the Ti3C2 nanosheets, improving the dispersion stability of Ti3C2 in the base oil, and having excellent friction reduction and anti-wear properties. The preparation method is simple and convenient, and high-quality lubricant additives can be obtained; it does not require expensive and complex instruments and strict and delicate experimental conditions, is environmentally friendly, and meets the requirements of green chemistry; the raw materials are cheap and easy to obtain, and it has good economy while also being a material with excellent lubricating effect; when in use, it only needs to be evenly dispersed in the base oil using ultrasound, which is easy to operate and conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.

[0010] Figure 1 A transmission electron microscope image of the lubricating oil additive according to Example 1 of the present application is shown; Figure 2 shows a scanning electron microscope image of the lubricating oil additive according to Example 1 of the present application; Figure 3 A stability chart of the lubricating oil additive in base oil according to Example 1 of the present application is shown; Figure 4 A comparative friction curve diagram showing the pure 500 SN base oil and the lubricating oil to which the lubricating oil additive is added according to Example 1 of the present application; Figure 5 A comparative photothermal conversion performance diagram of pure 500 SN base oil and lubricating oil with added lubricating oil additives according to Example 1 of the present application is shown; Figure 6A comparative Zeta potential diagram of Ti3C2 alone and COF@Ti3C2 according to Example 1 of the present application is shown; Figure 7 A comparative XRD potential diagram of Ti3C2 alone and COF@Ti3C2 according to Example 1 of the present application is shown. DETAILED DESCRIPTION

[0011] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.

[0012] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0013] According to an embodiment of the present application, a method for preparing a multifunctional lubricating oil additive is provided, the preparation method comprising: mixing Ti3C2 with tri(4-aminophenyl)amine and solvent A to obtain a mixed solution B; mixing the mixed solution B with 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione and solvent B to carry out a covalent organic framework synthesis reaction to obtain a lubricating oil additive.

[0014] Covalent organic framework materials are made of organic building blocks connected by covalent bonds, with high strength and low density. Their size can be controlled by adjusting the raw material ratio. This adjustability enables COF to adsorb or separate molecules of different sizes as needed, so that it can play the role of storing and releasing oil when used as a lubricant additive. In addition, COF also has high thermal and chemical stability and can maintain stable performance in harsh environments. This makes COF have a longer service life in many practical applications and reduces maintenance costs. Another raw material, Ti3C2, has low shear strength and is easy to form a wear-resistant friction layer. Its adhesion ability on different surfaces makes the contact passivated and significantly reduces interfacial adhesion. Therefore, Ti3C2 has good application prospects as a lubricant additive and solid lubricant coating.

[0015] In the lubricating oil additive, the covalent organic framework is in situ generated on titanium carbide, which not only increases the interlayer spacing of Ti3C2, but also forms a barrier on Ti3C2 to avoid its own accumulation. The prepared COF@Ti3C2 shows good dispersion stability in 500 SN. The friction coefficient and wear rate are reduced, and it has excellent anti-friction and anti-wear properties.

[0016] In some embodiments, the preparation method also includes a preparation method of Ti3C2, including: pre-treating MAX-Ti3AlC2 by adding the components to concentrated hydrochloric acid multiple times to obtain a pre-treated primary product; mixing the primary product with hydrofluoric acid for etching reaction to obtain Ti3C2. The acid etching degree of titanium carbide can be improved by adding the components to concentrated hydrochloric acid for pre-treatment multiple times.

[0017] In some embodiments, the mass volume ratio of the MAX-Ti3AlC2 and concentrated hydrochloric acid is 0.6-2.2g:5-15mL; the pretreatment time is 2-10min; the mass volume ratio of the MAX-Ti3AlC2 and hydrofluoric acid is 0.6-2.2g:5-15mL; the etching reaction time is 100-150h, and the etching reaction temperature is 90-100°C.

[0018] In some embodiments, during the etching reaction, the initial product is mixed with water, ethanol, and hydrofluoric acid, and the volume ratio of hydrofluoric acid, water, and ethanol is 5-15 mL: 5-12 mL: 5-15 mL. The etching reaction process can be ultrasonically treated, and the frequency of the ultrasonic treatment is 40-80 Hz, and the time of the ultrasonic treatment is 5-18 min.

[0019] In some embodiments, the product after the etching reaction is repeatedly subjected to ultrasonic treatment, centrifugation, and separation of the supernatant until the pH of the supernatant is 7.0-7.6 to obtain a precipitate. After the supernatant is separated, water is added, and then ultrasonication, centrifugation, and separation of the supernatant are performed. Further, the centrifugation speed is 4000-10000 rpm, and the time for each time is 5-18 min. The frequency of the ultrasonic treatment is 40-80 Hz, and the time for each time is 3-15 min. 20-40 mL of deionized water is added.

[0020] In some embodiments, the precipitate obtained after the etching reaction is subjected to ultrasonic centrifugation and separation of the supernatant is mixed with dimethyl sulfoxide and then centrifuged, the supernatant is separated, and dried to obtain Ti3C2. This process can be repeated 2 to 3 times. Freeze drying can be selected for drying. Furthermore, the centrifugation process has a speed of 4000-10000 rpm and a time of 5-18 min, and the frequency of the ultrasonic treatment is 40~80 Hz and the time is 3-15 min.

[0021] In some embodiments, the dimethyl sulfoxide washing is followed by water washing, and then the ultrasonic treatment, centrifugation, separation of the supernatant, and drying process are repeated. The centrifugation speed is 5000-10000 rpm, and the time for each time is 5-18 min; the frequency of the ultrasonic treatment is 40-80 Hz, and the time for each time is 3-15 min.

[0022] After washing with water, freeze drying is performed. In some embodiments, freeze drying is performed after washing with water, and then water is added, centrifuged, and freeze dried to obtain Ti3C2. The speed of the centrifugal process is 5000-10000 rpm, and the time of each time is 5-18 minutes.

[0023] In some embodiments, solvent A is one of methanol, n-propanol, ethyl acetate, toluene, xylene, and acetone; solvent B is one of chloroform, carbon tetrachloride, dichloromethane, ether, and tetrahydrofuran cyclohexanone; the mass volume ratio of tri(4-aminophenyl)amine to solvent A is 0.25-0.4 mg:1 mL; the mass volume ratio of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione to solvent B is 0.8-1.2 mg:1 mL.

[0024] In some embodiments, the molar ratio of tri(4-aminophenyl)amine to 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione is 1:1.2~2.0; the mass ratio of Ti3C2 to tri(4-aminophenyl)amine is 3-6:4-8.

[0025] In some embodiments, glacial acetic acid is added as a catalyst during the synthesis reaction of the covalent organic framework; the mass volume ratio of tri(4-aminophenyl)amine to glacial acetic acid is 1 mg:0.3-0.5 mL; and the synthesis reaction time of the covalent organic framework is 48-72 h.

[0026] In some embodiments, the solution after the synthesis reaction of the covalent organic framework is centrifuged and the supernatant is separated to obtain a substrate sediment; the bottom sediment is mixed with tetrahydrofuran and water, centrifuged, the supernatant is separated, and the lubricating oil additive is obtained after drying. The washing process using tetrahydrofuran and water can be repeated multiple times until the washing liquid is colorless.

[0027] According to an embodiment of the present application, there is also provided a lubricating oil additive prepared by the preparation method described in any embodiment of the present application.

[0028] According to an embodiment of the present application, there is also provided a use of the lubricating oil additive described in any embodiment of the present application in lubricating oil.

[0029] The lubricating oil additive can be applied to the lubricating oil to improve the lubricating performance and dispersion stability of the lubricating oil. In some embodiments, the mass fraction of the lubricating oil additive in the lubricating oil is 0.05%-0.15%. As an additive, the lubricating oil additive has high lubricating activity, and when the concentration in the lubricating oil is 0.125 wt%, the friction reduction and anti-wear effect of the lubricating oil can be significantly improved.

[0030] In some embodiments, the lubricating oil includes a base oil, and the base oil includes a variety of base oils such as a mineral base oil, a synthetic base oil and / or a vegetable oil base oil.

[0031] The mixing method of the lubricating oil additive and the base oil of the present application: the lubricating oil additive is dispersed into the base oil by ultrasound or stirring. The dispersing method of the lubricating oil additive of the present application is simple and easy to operate.

[0032] Example 1 (1) Synthesis of Ti3C2 Preparation of titanium carbide: 10 mL of concentrated hydrochloric acid was added to a polytetrafluoroethylene-lined reactor, 1.2 g of MAX-Ti3AlC2 powder was dispersed in concentrated hydrochloric acid in small amounts for multiple times for pretreatment, and after standing for 5 min, 12 mL of hydrofluoric acid was added, and 5 mL of deionized water and 5 mL of anhydrous ethanol were added to a polytetrafluoroethylene beaker, and ultrasonic treatment was performed at a frequency of 60 Hz for 10 min. After mixing evenly, it was poured into a polytetrafluoroethylene-lined reactor, and after being fully mixed, it was placed in an oven and heated at 100 ° C for 120 h. After the reaction was completed, it was cooled to room temperature, and the product was ultrasonically treated at a frequency of 60 Hz for 10 min, and then centrifuged at a speed of 4000 rpm for 12 min. After centrifugation, the strong acid product of the supernatant was poured out to obtain a precipitate. Add 30 mL of ionized water to the precipitate in the centrifuge tube and mix well, then perform ultrasonic treatment at a frequency of 60 Hz for 10 min, and centrifuge at a speed of 6000 rpm for 12 min, repeat several times until the pH value of the solution in the centrifuge tube is about 7.4. Add 25 mL of dimethyl sulfoxide (DMSO) to the washed precipitate, stir at room temperature for 48 h, perform ultrasonic treatment at a frequency of 60 Hz for 10 min, and then centrifuge at a speed of 6000 rpm for 12 min to filter out the solid product. Add 30 mL of deionized water to the filtered solid product, then perform ultrasonic treatment at a frequency of 60 Hz for 10 min, and then centrifuge at a speed of 10000 rpm for 12 min, repeat 3 times to obtain a solid product, and then freeze-dry, repeat the centrifugal washing process (speed 6000 rpm, 10 min) 3 times, perform secondary freeze-drying, and titanium carbide solid can be obtained for standby use.

[0033] (2) Synthesis of COF@Ti3C20.16 / 0.07 After taking 20 mg of Ti3C2 powder and placing it in a beaker, add 32 mg of tri(4-aminophenyl)amine to the beaker, and then add 105 mL of methanol to completely dissolve and adsorb it onto the Ti3C2 nanosheets; weigh 93 mg of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, add it to the above beaker, and then add 103 mL of chloroform. Then ultrasonic treatment (frequency 60 Hz, 10 min) was performed. After the above two solutions were mixed, 15 mL of glacial acetic acid was added to catalyze the reaction, placed on a magnetic stirrer for 5 min, and placed in a cool and dark place for 48 h. After the reaction was completed, the solution turned dark purple. The solution was centrifuged in a centrifuge at 8000 rpm for 12 min. The supernatant in the centrifuge tube was removed, 60 mL of tetrahydrofuran was added for washing, and centrifugation was continued. This operation was repeated three times. The tetrahydrofuran washing solution was almost colorless. After removing the supernatant, the bottom sediment was washed with deionized water and centrifuged several times to remove the unreacted reagent. The bottom sediment was freeze-dried to obtain COF@Ti3C2 powder.

[0034] The transmission electron microscope image of the COF@Ti3C2 powder obtained in Example 1 is as follows Figure 1 As shown, it can be seen that the particle size of the synthesized lubricating oil additive material is uniform, with a particle diameter of approximately 150 nm, and COF can be observed attached to the Ti3C2 nanosheets.

[0035] The scanning electron microscope image of the COF@Ti3C2 powder obtained in Example 1 is as follows Figure 2 As shown, it can be seen that the synthesized lubricating oil additive material has a regular shape, is well dispersed, and has a particle size of approximately 130 nm.

[0036] The COF@Ti3C2 powder obtained in Example 1 was ultrasonically mixed with 500 SN base oil. The dispersion stability results are as follows: Figure 3 As shown, through Figure 3 It can be seen that after standing for 7 days, the powder still showed stable dispersion. After standing for 14 days, COF@Ti3C2 showed a small amount of sedimentation. Therefore, the COF@Ti3C2 powder of the present application showed excellent dispersion stability.

[0037] (3) Tribological test The COF@Ti3C2 powder obtained in step (2) was dissolved in 500 SN base oil and dispersed evenly as lubricant (the mass fraction of COF@Ti3C2 powder in the lubricant was 0.125 wt%). The tribological properties of the steel / steel contact point were analyzed using a CFT-I friction machine. The upper ball was a GCr-15 steel ball, and the lower plate was a steel block of the same material, polished with a metallographic polishing cloth at 300 rpm. Test conditions: temperature 25 °C, frequency 1 Hz, amplitude 2 mm, load 50 N. The morphology and wear of the scratches were tested using a three-dimensional profile surface analyzer.

[0038] The test results show that the scratches on the steel block are smooth and there are no wide and deep grooves, and the wear loss is less than 15% (compared to the original steel block). Therefore, the COF@Ti3C2 powder of the present application has a good anti-friction and anti-wear effect.

[0039] The 500 SN base oil alone and the lubricating oil obtained by adding COF@Ti3C2 of Example 1 to the 500 SN base oil (the mass fraction of COF@Ti3C2 powder in the lubricating oil was 0.125 wt%) were respectively analyzed for tribological properties using a CFT-I friction machine. The test conditions were: temperature 25 °C, frequency 1 Hz, amplitude 2 mm, load 125 N. The following results were obtained: Figure 4 The results shown are as follows: Figure 4 As shown, through Figure 4 It can be seen that after adding COF@Ti3C2, the friction coefficient is greatly reduced and remains stable. The friction coefficient and wear rate are reduced by about 18.2% and 84.0% respectively. Therefore, the COF@Ti3C2 powder of the present application has a good friction reduction and anti-wear effect.

[0040] (4) Photothermal performance test The test tubes with pure 500 SN oil and the test tubes with 0.125 wt% COF@Ti3C2 added to 500 SN oil were fixed at a power of 1.0 W / cm 2 The irradiation distance was 8 cm and the room temperature was 25 °C. A contact thermometer was used to record the temperature of the composite system every 30 seconds at a distance of 1 cm from the irradiation focus. The results are shown in Figure 5 As shown, through Figure 5 It can be obtained at 1 W / cm 2 Under the irradiation of near-infrared light, the temperature of the 0.125 wt% lubricating system rises quickly to 62.5°C. In contrast, the temperature of the pure 500 SN base oil does not change much. This indicates that the COF@Ti3C2 heterogeneous composite structure can absorb and convert near-infrared light with high efficiency.

[0041] The Ti3C2 and COF@Ti3C2 powders of Example 1 were tested for Zeta potential respectively. The results are as follows: Figure 6 The results shown by Figure 6 It can be obtained that the Zeta potential value of COF@Ti3C2 is −27.3 mV, which is lower than −13.2 mV of Ti3C2. This difference further proves that COF is successfully attached to the surface of Ti3C2.

[0042] The COF@Ti3C2 powder of Example 1 was subjected to XRD detection and the following results were obtained: Figure 7 The results shown by Figure 7 It can be seen that compared with Ti3C2, the diffraction peak angle shift of the (002) crystal plane of COF@Ti3C2 is lower due to interlayer expansion. At the same time, it is confirmed that the layered structure of Ti3C2 is not destroyed after composite.

[0043] Example 2 (1) Synthesis of Ti3C2 Preparation of titanium carbide: 10 mL of concentrated hydrochloric acid was added to a polytetrafluoroethylene-lined reactor, and 1.8 g of MAX-Ti3AlC2 powder was dispersed in concentrated hydrochloric acid in small amounts for multiple times for pretreatment. After standing for 5 min, 13 mL of hydrofluoric acid was added, and 6 mL of deionized water and 6 mL of anhydrous ethanol were added to a polytetrafluoroethylene beaker. Ultrasonic treatment was performed at a frequency of 60 Hz for 12 min, and the mixture was poured into a polytetrafluoroethylene-lined reactor after being mixed evenly. After being fully mixed, the mixture was placed in an oven and heated at 100 °C for 120 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was ultrasonically treated at a frequency of 60 Hz for 12 min, and then centrifuged at a speed of 4000 rpm for 15 min. After centrifugation, the strong acid product in the supernatant was poured out to obtain a precipitate. Add 30 mL of ionized water to the precipitate in the centrifuge tube and mix well, then perform ultrasonic treatment at a frequency of 60 Hz for 12 min, and centrifuge at a speed of 6000 rpm for 15 min, repeat several times until the pH value of the solution in the centrifuge tube is about 7.4. Add 30 mL of dimethyl sulfoxide (DMSO) to the washed precipitate, stir at room temperature for 48 h, perform ultrasonic treatment at a frequency of 60 Hz for 12 min, and then centrifuge at a speed of 6000 rpm for 15 min to filter out the solid product. Add 30 mL of deionized water to the filtered solid product, then perform ultrasonic treatment at a frequency of 60 Hz for 12 min, and then centrifuge at a speed of 10000 rpm for 15 min, repeat 3 times to obtain a solid product, and then freeze-dry, repeat the centrifugal washing process (speed 6000 rpm, 12 min) 3 times, perform secondary freeze-drying, and titanium carbide solid can be obtained for standby use.

[0044] (2) Synthesis of COF@Ti3C2 After taking 20 mg of Ti3C2 powder and placing it in a beaker, add 25 mg of tri(4-aminophenyl)amine to the beaker, and then add 80 mL of methanol to completely dissolve and adsorb it to the Ti3C2 nanosheets; weigh 83 mg of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, add it to the above beaker, and then add 80 mL of chloroform. Then ultrasonic treatment (frequency 60 Hz, 8 min) was performed. After the above two solutions were mixed, 10 mL of glacial acetic acid was added to catalyze the reaction, placed on a magnetic stirrer for 5 min, and placed in a cool and dark place for 60 h. After the reaction was completed, the solution turned dark purple. The solution was centrifuged in a centrifuge at 7500 rpm for 15 min. The supernatant in the centrifuge tube was removed, 45 mL of tetrahydrofuran was added for washing, and centrifugation was continued. This operation was repeated three times. The tetrahydrofuran washing solution was almost colorless. After removing the supernatant, the bottom sediment was washed with deionized water and centrifuged several times to remove the unreacted reagent. The bottom sediment was freeze-dried to obtain COF@Ti3C2 powder.

[0045] (3) Tribological test The COF@Ti3C2 powder obtained in step (2) was dissolved in 500 SN base oil and dispersed evenly as lubricant (the mass fraction of COF@Ti3C2 powder in the lubricant was 0.05 wt%). The tribological properties of the steel / steel contact point were analyzed using a CFT-I friction machine. The upper ball was a GCr-15 steel ball, and the lower plate was a steel block of the same material, polished with a metallographic polishing cloth at 300 rpm. Test conditions: temperature 25 °C, frequency 2 Hz, amplitude 2 mm, load 75 N. The morphology and wear of the scratches were tested using a three-dimensional profile surface analyzer.

[0046] The test results show that the scratches on the steel block are smooth and there are no wide and deep grooves, and the wear amount is less than 60% (compared to the original steel block). Therefore, the COF@Ti3C2 powder of the present application has a good anti-friction and anti-wear effect.

[0047] (4) Photothermal performance test The test tubes with pure 500 SN oil and the test tubes with 0.05 wt% COF@Ti3C2 added to 500 SN oil were fixed at a power of 1.0 W / cm 2 The infrared light was directly irradiated. The irradiation distance was 8 cm and the room temperature was 25 °C. A contact thermometer was used to record the temperature of the composite system every 30 s at a distance of 1.5 cm from the irradiation focus.

[0048] Example 3 (1) Synthesis of Ti3C2 Preparation of titanium carbide: 10 mL of concentrated hydrochloric acid was added to a polytetrafluoroethylene-lined reactor, and 0.8 g of MAX-Ti3AlC2 powder was dispersed in concentrated hydrochloric acid in small amounts for pretreatment. After standing for 5 min, 9 mL of hydrofluoric acid was added, and 4 mL of deionized water and 4 mL of anhydrous ethanol were added to the polytetrafluoroethylene beaker, and ultrasonic treatment was performed at a frequency of 60 Hz for 8 min. After mixing evenly, the mixture was poured into a polytetrafluoroethylene-lined reactor, and after being fully mixed, the mixture was placed in an oven and heated at 100 °C for 120 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was ultrasonically treated at a frequency of 60 Hz for 8 min, and then centrifuged at a speed of 4000 rpm for 10 min. After centrifugation, the strong acid product of the supernatant was discarded to obtain a precipitate. 30 mL of ionized water was added to the precipitate in the centrifuge tube and mixed evenly, and then ultrasonic treatment was performed at a frequency of 60 Hz for 8 min, and centrifuged at a speed of 6000 rpm for 10 min. This was repeated several times until the pH value of the solution in the centrifuge tube was about 7.4. Add 20 mL of dimethyl sulfoxide (DMSO) to the washed precipitate, stir at room temperature for 48 h, ultrasonically treat the stirred solution at a frequency of 60 Hz for 8 min, and then centrifuge at a speed of 6000 rpm for 10 min to filter out the solid product. Add 30 mL of deionized water to the filtered solid product, then ultrasonically treat at a frequency of 60 Hz for 8 min, and then centrifuge at a speed of 10000 rpm for 10 min, repeat 3 times to obtain a solid product, and then freeze-dry, repeat the centrifugal washing process (speed 6000 rpm, 8 min) 3 times, and perform secondary freeze-drying to obtain titanium carbide solid for use.

[0049] (2) Synthesis of COF@Ti3C2 After taking 22 mg of Ti3C2 powder and placing it in a beaker, add 32 mg of tri(4-aminophenyl)amine to the beaker, and then add 105 mL of n-propanol to completely dissolve and adsorb it onto the Ti3C2 nanosheets; weigh 100 mg of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, add it to the above beaker, and then add 100 mL of carbon tetrachloride. Then ultrasonic treatment (frequency 60 Hz, 10 min) was performed. After the above two solutions were mixed, 11 mL of glacial acetic acid was added to catalyze the reaction, placed on a magnetic stirrer for 5 min, and placed in a cool and dark place for 72 hours. After the reaction was completed, the solution turned dark purple. The solution was centrifuged in a centrifuge at 8000 rpm for 15 min. The supernatant in the centrifuge tube was removed, 60 mL of tetrahydrofuran was added for washing, and centrifugation was continued. This operation was repeated three times. The tetrahydrofuran washing solution was almost colorless. After removing the supernatant, the bottom sediment was washed with deionized water and centrifuged several times to remove the unreacted reagent. The bottom sediment was freeze-dried to obtain COF@Ti3C2 powder.

[0050] (3) Tribological test The COF@Ti3C2 powder obtained in step (2) was dissolved in 500 SN base oil and dispersed evenly as lubricant (the mass fraction of COF@Ti3C2 powder in the lubricant was 0.075 wt%). The tribological properties of the steel / steel contact point were analyzed using a CFT-I friction machine. The upper ball was a GCr-15 steel ball, and the lower plate was a steel block of the same material, polished with a metallographic polishing cloth at 300 rpm. Test conditions: temperature 25 °C, frequency 3 Hz, amplitude 2 mm, load 100 N. The morphology and wear of the scratches were tested using a three-dimensional profile surface analyzer.

[0051] The test results show that the scratches on the steel block are smooth and there are no wide and deep grooves, and the wear loss is less than 55% (compared to the original steel block). Therefore, the COF@Ti3C2 powder of the present application has a good anti-friction and anti-wear effect.

[0052] (4) Photothermal performance test The test tubes with pure 500 SN oil and the test tubes with 0.075 wt% COF@Ti3C2 added to 500 SN oil were fixed at a power of 1.0 W / cm 2 The infrared light was directly irradiated. The irradiation distance was 10 cm and the room temperature was 25 °C. A contact thermometer was used to record the temperature of the composite system every 30 s at a distance of 1 cm from the irradiation focus.

[0053] Example 4 (1) Synthesis of Ti3C2 Preparation of titanium carbide: 10 mL of concentrated hydrochloric acid was added to a polytetrafluoroethylene-lined reactor, and 0.8 g of MAX-Ti3AlC2 powder was dispersed in concentrated hydrochloric acid in small amounts for pretreatment. After standing for 5 min, 9 mL of hydrofluoric acid was added, and 4 mL of deionized water and 4 mL of anhydrous ethanol were added to the polytetrafluoroethylene beaker. Ultrasonic treatment was performed at a frequency of 60 Hz for 8 min, and the mixture was poured into the polytetrafluoroethylene-lined reactor. After being fully mixed, the mixture was placed in an oven and heated at 90 °C for 120 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was ultrasonically treated at a frequency of 60 Hz for 8 min, and then centrifuged at a speed of 3800 rpm for 10 min. After centrifugation, the strong acid product of the supernatant was discarded to obtain a precipitate. 30 mL of ionized water was added to the precipitate in the centrifuge tube and mixed evenly, and then ultrasonically treated at a frequency of 60 Hz for 8 min, and centrifuged at a speed of 6000 rpm for 10 min. This was repeated several times until the pH value of the solution in the centrifuge tube was about 7.4. Add 20 mL of dimethyl sulfoxide (DMSO) to the washed precipitate, stir at room temperature for 24 h, ultrasonically treat the stirred solution at a frequency of 60 Hz for 8 min, and then centrifuge at a speed of 6000 rpm for 10 min to filter out the solid product. Add 30 mL of deionized water to the filtered solid product, then ultrasonically treat at a frequency of 60 Hz for 8 min, and then centrifuge at a speed of 10000 rpm for 10 min, repeat 3 times to obtain a solid product, and then freeze-dry, repeat the centrifugal washing process (speed 6000 rpm, 8 min) 3 times, and perform secondary freeze-drying to obtain titanium carbide solid for use.

[0054] (2) Synthesis of COF@Ti3C2 After taking 20 mg of Ti3C2 powder and placing it in a beaker, add 32 mg of tri(4-aminophenyl)amine to the beaker, and then add 105 mL of ethyl acetate to completely dissolve and adsorb it onto the Ti3C2 nanosheets; weigh 75 mg of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, add it to the above beaker, and then add 85 mL of chloroform. Then ultrasonic treatment (frequency 60 Hz, 10 min) was performed. After the above two solutions were mixed, 12 mL of glacial acetic acid was added to catalyze the reaction, placed on a magnetic stirrer for 5 min, and placed in a cool and dark place for 48 h. After the reaction was completed, the solution turned dark purple. The solution was centrifuged in a centrifuge at 8000 rpm for 15 min. The supernatant in the centrifuge tube was removed, 60 mL of tetrahydrofuran was added for washing, and centrifugation was continued. This operation was repeated three times. The tetrahydrofuran washing solution was almost colorless. After removing the supernatant, the bottom sediment was washed with deionized water and centrifuged several times to remove the unreacted reagent. The bottom sediment was freeze-dried to obtain COF@Ti3C2 powder.

[0055] (3) Tribological test The COF@Ti3C2 powder obtained in step (2) was dissolved in 500 SN base oil and dispersed evenly as lubricant (the mass fraction of COF@Ti3C2 powder in the lubricant was 0.1 wt%). The tribological properties of the steel / steel contact point were analyzed using a CFT-I friction machine. The upper ball was a GCr-15 steel ball, and the lower plate was a steel block of the same material, polished with a metallographic polishing cloth at 300 rpm. Test conditions: temperature 25 °C, frequency 4 Hz, amplitude 2 mm, load 125 N. The morphology and wear of the scratches were tested using a three-dimensional profile surface analyzer.

[0056] The test results show that the scratches on the steel block are smooth and there are no wide and deep grooves, and the wear loss is less than 47% (compared to the original steel block). Therefore, the COF@Ti3C2 powder of the present application has a good anti-friction and anti-wear effect.

[0057] (4) Photothermal performance test The test tubes with pure 500 SN oil and the test tubes with 0.1 wt% COF@Ti3C2 added to 500 SN oil were fixed at a power of 1.0 W / cm 2 The infrared light was directly irradiated. The irradiation distance was 10 cm and the room temperature was 25 °C. A contact thermometer was used to record the temperature of the composite system every 30 s at a distance of 1.5 cm from the irradiation focus.

[0058] Example 5 (1) Synthesis of Ti3C2 Preparation of titanium carbide: 10 mL of concentrated hydrochloric acid was added to a polytetrafluoroethylene-lined reactor, and 1.8 g of MAX-Ti3AlC2 powder was dispersed in concentrated hydrochloric acid in small amounts for multiple times for pretreatment. After standing for 5 min, 15 mL of hydrofluoric acid was added, and 6 mL of deionized water and 6 mL of anhydrous ethanol were added to a polytetrafluoroethylene beaker. Ultrasonic treatment was performed at a frequency of 80 Hz for 12 min, and the mixture was poured into a polytetrafluoroethylene-lined reactor after being mixed evenly. After being fully mixed, the mixture was placed in an oven and heated at 100 °C for 120 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was ultrasonically treated at a frequency of 80 Hz for 12 min, and then centrifuged at a speed of 4500 rpm for 15 min. After centrifugation, the strong acid product in the supernatant was poured out to obtain a precipitate. Add 30 mL of ionized water to the precipitate in the centrifuge tube and mix well, then perform ultrasonic treatment at a frequency of 80 Hz for 12 min, and centrifuge at a speed of 6000 rpm for 15 min, repeat several times until the pH value of the solution in the centrifuge tube is about 7.4. Add 25 mL of dimethyl sulfoxide (DMSO) to the washed precipitate, stir at room temperature for 48 h, perform ultrasonic treatment at a frequency of 80 Hz for 12 min, and then centrifuge at a speed of 6000 rpm for 15 min to filter out the solid product. Add 30 mL of deionized water to the filtered solid product, then perform ultrasonic treatment at a frequency of 80 Hz for 12 min, and then centrifuge at a speed of 10000 rpm for 15 min, repeat 3 times to obtain a solid product, and then freeze-dry, repeat the centrifugal washing process (speed 6000 rpm, 12 min) 3 times, perform secondary freeze-drying, and titanium carbide solid can be obtained for standby use.

[0059] (2) Synthesis of COF@Ti3C2 After taking 20 mg of Ti3C2 powder and placing it in a beaker, add 32 mg of tri(4-aminophenyl)amine to the beaker, and then add 105 mL of toluene to completely dissolve and adsorb it onto the Ti3C2 nanosheets; weigh 92 mg of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, add it to the above beaker, and then add 103 mL of ether. Then ultrasonic treatment (frequency 60 Hz, 10 min) was performed. After the above two solutions were mixed, 15 mL of glacial acetic acid was added to catalyze the reaction, placed on a magnetic stirrer for 5 min, and placed in a cool and dark place for 60 h. After the reaction was completed, the solution turned dark purple. The solution was centrifuged in a centrifuge at 8000 rpm for 15 min. The supernatant in the centrifuge tube was removed, 60 mL of tetrahydrofuran was added for washing, and centrifugation was continued. This operation was repeated three times. The tetrahydrofuran washing solution was almost colorless. After removing the supernatant, the bottom sediment was washed with deionized water and centrifuged several times to remove the unreacted reagent. The bottom sediment was freeze-dried to obtain COF@Ti3C2 powder.

[0060] (3) Tribological test The COF@Ti3C2 powder obtained in step (2) was dissolved in 500 SN base oil and dispersed evenly as lubricant (the mass fraction of COF@Ti3C2 powder in the lubricant was 0.15 wt%). The tribological properties of the steel / steel contact point were analyzed using a CFT-I friction machine. The upper ball was a GCr-15 steel ball, and the lower plate was a steel block of the same material, polished with a metallographic polishing cloth at 300 rpm. Test conditions: temperature 25 °C, frequency 5 Hz, amplitude 2 mm, load 150 N. The morphology and wear of the scratches were tested using a three-dimensional profile surface analyzer.

[0061] The test results show that the scratches on the steel block are smooth and there are no wide and deep grooves, and the wear amount is less than 30% (compared to the original steel block). Therefore, the COF@Ti3C2 powder of the present application has a good anti-friction and anti-wear effect.

[0062] (4) Photothermal performance test The test tubes with pure 500 SN oil and the test tubes with 0.125 wt% COF@Ti3C2 added to 500 SN oil were fixed at a power of 1.0 W / cm 2 The infrared light was directly irradiated. The irradiation distance was 12 cm and the room temperature was 25 °C. A contact thermometer was used to record the temperature of the composite system every 30 s at a distance of 1 cm from the irradiation focus.

[0063] Example 6 (1) Synthesis of Ti3C2 Preparation of titanium carbide: 10 mL of concentrated hydrochloric acid was added to a polytetrafluoroethylene-lined reactor, 1.2 g of MAX-Ti3AlC2 powder was dispersed in concentrated hydrochloric acid in small amounts for multiple times for pretreatment, and after standing for 5 min, 10 mL of hydrofluoric acid was added, and 5 mL of deionized water and 5 mL of anhydrous ethanol were added to a polytetrafluoroethylene beaker, and ultrasonic treatment was performed at a frequency of 60 Hz for 10 min. After mixing evenly, it was poured into a polytetrafluoroethylene-lined reactor, and after being fully mixed, it was placed in an oven and heated at 90 ° C for 120 h. After the reaction was completed, it was cooled to room temperature, and the product was ultrasonically treated at a frequency of 60 Hz for 10 min, and then centrifuged at a speed of 4000 rpm for 12 min. After centrifugation, the strong acid product of the supernatant was poured out to obtain a precipitate. Add 30 mL of ionized water to the precipitate in the centrifuge tube and mix well, then perform ultrasonic treatment at a frequency of 60 Hz for 10 min, and centrifuge at a speed of 6000 rpm for 12 min, repeat several times until the pH value of the solution in the centrifuge tube is about 7.4. Add 30 mL of dimethyl sulfoxide (DMSO) to the washed precipitate, stir at room temperature for 24 h, perform ultrasonic treatment at a frequency of 60 Hz for 10 min, and then centrifuge at a speed of 6000 rpm for 12 min to filter out the solid product. Add 30 mL of deionized water to the filtered solid product, then perform ultrasonic treatment at a frequency of 60 Hz for 10 min, and then centrifuge at a speed of 10000 rpm for 12 min, repeat 3 times to obtain a solid product, and then freeze-dry, repeat the centrifugal washing process (speed 6000 rpm, 10 min) 3 times, perform secondary freeze-drying, and titanium carbide solid can be obtained for standby use.

[0064] (2) Synthesis of COF@Ti3C2 After taking 20 mg of Ti3C2 powder and placing it in a beaker, add 25 mg of tri(4-aminophenyl)amine to the beaker, and then add 80 mL of methanol to completely dissolve and adsorb it onto the Ti3C2 nanosheets; weigh 80 mg of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, add it to the above beaker, and then add 85 mL of tetrahydrofuran. Then ultrasonic treatment (frequency 60 Hz, 10 min) was performed. After the above two solutions were mixed, 15 mL of glacial acetic acid was added to catalyze the reaction, placed on a magnetic stirrer for 5 min, and placed in a cool and dark place for 48 h. After the reaction was completed, the solution turned dark purple. The solution was centrifuged in a centrifuge at 8000 rpm for 10 min. The supernatant in the centrifuge tube was removed, 50 mL of tetrahydrofuran was added for washing, and centrifugation was continued. This operation was repeated three times. The tetrahydrofuran washing solution was almost colorless. After removing the supernatant, the bottom sediment was washed with deionized water and centrifuged several times to remove the unreacted reagent. The bottom sediment was freeze-dried to obtain COF@Ti3C2 powder.

[0065] (3) Tribological test The COF@Ti3C2 powder obtained in step (2) was dissolved in 500 SN base oil and evenly dispersed as lubricant. The tribological properties of the steel / steel contact point were analyzed using a CFT-I friction machine. The upper ball was a GCr-15 steel ball, and the lower plate was a steel block of the same material, polished at 300 rpm with a metallographic polishing cloth. Test conditions: temperature 25 °C, frequency 1 Hz, amplitude 2 mm, load 75 N. The morphology and wear of the scratches were tested using a three-dimensional profile surface analyzer.

[0066] The test results show that the scratches on the steel block are smooth and there are no wide and deep grooves, and the wear amount is less than 20% (compared to the original steel block). Therefore, the COF@Ti3C2 powder of the present application has a good anti-friction and anti-wear effect.

[0067] (4) Photothermal performance test The test tubes with pure 500 SN oil and the test tubes with 0.125 wt% COF@Ti3C2 added to 500 SN oil were fixed at a power of 1.0 W / cm 2 The infrared light was directly irradiated. The irradiation distance was 12 cm and the room temperature was 25 °C. A contact thermometer was used to record the temperature of the composite system every 30 s at a distance of 1.5 cm from the irradiation focus.

[0068] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.

[0069] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.

[0070] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A method for preparing a multifunctional lubricating oil additive, characterized in that: The preparation method comprises: mixing Ti3C2 with tri(4-aminophenyl)amine and solvent A to obtain a mixed solution B; mixing the mixed solution B with 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione and solvent B to carry out a synthesis reaction of a covalent organic framework to obtain a lubricating oil additive.

2. The preparation method according to claim 1, characterized in that: The preparation method also includes a preparation method of Ti3C2, including: pre-treating MAX-Ti3AlC2 by adding the components into concentrated hydrochloric acid multiple times to obtain a pre-treated primary product; mixing the primary product with hydrofluoric acid to perform an etching reaction to obtain Ti3C2.

3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the MAX-Ti3AlC2 and concentrated hydrochloric acid is 0.6-2.2 g:5-15 mL; the pretreatment time is 2-10 min; the mass volume ratio of the MAX-Ti3AlC2 and hydrofluoric acid is 0.6-2.2 g:5-15 mL; the etching reaction time is 100-150 h, and the etching reaction temperature is 90-100 °C.

4. The preparation method according to claim 1, characterized in that: Solvent A is one of methanol, n-propanol, ethyl acetate, toluene, xylene, and acetone; solvent B is one of chloroform, carbon tetrachloride, dichloromethane, ether, tetrahydrofuran, and cyclohexanone.

5. The preparation method according to claim 1, characterized in that: The mass volume ratio of tri(4-aminophenyl)amine to solvent A is 0.25-0.4 mg:1 mL; the mass volume ratio of 3,6-bis(5-formylthiophen-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione to solvent B is 0.8-1.2 mg:1 mL.

6. The preparation method according to claim 1, characterized in that: The molar ratio of tri(4-aminophenyl)amine to 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione is 1:1.2-2.

0.

7. The preparation method according to claim 1, characterized in that: The mass ratio of Ti3C2 and tris(4-aminophenyl)amine is 3-6:4-8.

8. The preparation method according to claim 1, characterized in that: Glacial acetic acid is added as a catalyst in the synthesis reaction of the covalent organic framework; the mass volume ratio of tri(4-aminophenyl)amine to glacial acetic acid is 1 mg:0.3-0.5 mL; and the synthesis reaction time of the covalent organic framework is 48-72 h.

9. The lubricating oil additive prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the lubricating oil additive according to claim 9 in lubricating oil.